Programmed cell death in castor bean endosperm is associated with the accumulation and release of a cysteine endopeptidase from ricinosomes - Schmid, Markus (National Academy of Sciences, 1999)
The cells of the endosperm of castor bean seeds (Ricinus communis) undergo programmed cell death during germination, after their oil and protein reserves have been mobilized. Nuclear DNA fragmentation first was observed at day 3 in the endosperm cells immediately adjacent to the cotyledons and progressed across to the outermost cell layers by day 5. We also detected the accumulation of small organelles known as ricinosomes, by using an antibody against a cysteine endoprotease. By the time the nuclear DNA was susceptible to heavy label by terminal deoxynucleotidyltransferase-mediated dUTP nick end labeling, the ricinosomes had released into the cytoplasm their content of cysteine endoprotease, which became activated because of the cleavage of its propeptide. The cysteine endoprotease is distinguished by a C-terminal KDEL sequence, although it is not retained in the lumen of the endoplasmic reticulum and is a marker for ricinosomes. Homologous proteases are found in the senescing tissues of other plants, including the petals of the daylily. Ricinosomes were identified in this tissue by electron microscopy and immunocytochemistry. It seems that ricinosomes are not unique to Ricinus and play an important role in the degradation of plant cell contents during programmed cell death.